Inovasi Model dan Strategi Pembelajaran pada Mata Pelajaran Fiqih di MA Nizhamiyah Ploso Jombang - Ahmad Bahrul Musyaffak; Mohammad Saat Ibnu Waqfin (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Updating learning models and strategies in education is very important to suit the digital era, this is one of the supporting and inhibiting factors to continue to spur new innovations in learning models and strategies. so it becomes an answer with time. in educational foundations. Learning models and strategies are often applied by teachers using monotonous learning models, especially in Islamic jurisprudence subjects. It is necessary for the teacher to know about new innovations in learning models and strategies so that students understand the problems of fiqh which are always increasing with the times. The refore this research aims to: 1) find out the innovation of learning models and their application to fiqh subjects at MA Nizhamiyah. 2) to find out the innovative learning strategies and their application to fiqh subjects at MA Nizhamiyah. 3) to find out the inhibiting factors in model innovation and learning strategies in fiqh subjects at MA Nizhamiyah. In this study, the researcher took the title